Actualización del protocolo para elementos de red en el modelo digital de energía G/Technology (2023)
This project aims to define the work procedure for updating the CENS G/Technology digital model where all electrical energy assets are modeled and entered and left for the operation of the CDL, this will serve as a learning base for the entire team. company personnel, whether plant or contractor, who enters new and has to update on the application, so that when carrying out activities that will serve as a guide for the companies of the EPM group, interested in ensuring the resources and effective operation of all their assets, guaranteeing the sustainability of the company based on the reports of its Investment plans stipulated by the regulatory framework of CREG015 of 2018, which requires all companies to make an investment plan for assets in the electrical part that will have a life period of until 35 years which must be reported through the commissioning reports in MDE where all the Georeferenced assets are held.